Characterization of enzyme produced by Pseudomonas putida in treating mercury form petrochemical wastewater - Azoddein, Abdul Aziz Mohd; Yunus, Rosli Mohd (2017)
Mercury is one of the toxic element and very harmful. The exposure of the mercury will mainly cause health effect and the exposure can be in term of dose, age of person exposed, duration exposed route exposed and duration of exposed. In Malaysia, Mercury is one of the heavy metals of concern, found in wastewaters coming from oil refinery and petrochemical industries. Mercury and mercurial compounds are highly toxic contaminants in the aquatic systems and soils. The proper disposal of wastewater should be implement with the Department of Environment of Malaysia (DOE) which is the concentration of mercury should be 0.05 ppm for standard B in wastewater for the sake of people and environment health. There are many types of mercury removal technology to reduce the concentration of mercury such as chemical treatment, ion exchange, membrane filtration, adsorption as well as bioremediation which used for mercury removal in this study. This paper present the activity of enzyme from P. putida is produced in the mercury treatment from petrochemical wastewater at optimum condition. Three different concentration of mercury which were 3 ppm, 5 ppm and 7 ppm were exposed to various temperature and shaker speed. The temperature study was measured at 33 ˚C, 37 ˚C and 41 ˚C while for speed shaker were at 140 rpm, 180 rpm and 220 rpm. P. putida growth at optimum condition in mercury different concentration was observed. Conclusion, optimum condition concentration of mercury and shaker speed at 3 ppm is 37 ˚C and 140 rpm respectively, with able to reduce 86.13 % mercury concentration. Optimum condition concentration of mercury and shaker speed at 5 ppm is 41 ˚C and 180 rpm respectively, with able to reduce 71.47 % mercury concentration. Lastly, optimum condition concentration of mercury and shaker speed at 7 ppm is 41 ˚C and 180 rpm respectively, with able to reduce 92.59 % mercury concentration. During the processes of mercury removal, mercuric reductase was produced at value of 56 kDa.